The Influence of Innovative Leaders as Communication Development Agent in Leveraging Digital Technology Use Amongst Indonesian Teachers - Unasiansari, Ismia; Sarwoprasodjo, Sarwititi; Kinseng, Rilus; Sadono, Dwi (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2024)
Teacher's digital technology use has become an enormous challenge in the school digital transformation program process. This study aims to analyze the emerging role of innovative leadership in influencing digital technology use and to test the relationship between innovative leadership, perceived usefulness, perceived ease of use, and digital technology use among teachers at the Sekolah Penggerak program in Indonesia. This study explores a modified technology acceptance model as the theoretical framework. Three hundred ninety-seven teachers participated in this research through a simple random sampling method. The study results show the significant role of innovative leadership in influencing teachers' digital technology use when mediated by perceived usefulness and perceived ease of use with a p-value of 0,000. Innovative leadership continuously has a significant direct effect on perceived usefulness, with a value of 0,000. It also shows positive effects on perceived ease of use with a value of 0,000. Moreover, data analysis shows that innovative leadership is perceived as sufficiently high, with a scale of 4,22 out of 5 points. Furthermore, being skilful at team building is perceived as a powerful indicator, contributing 4,25 out of 5 points. Not only team building, being visionary, skilful at relationship building, and confident at risk-taking is also statistically proven to be sufficient, with score results of 4,22, 4,21, and 4,21 for each indicator. Teachers' digital technology use also reached 3.82 out of a 5-point scale, which shows high results on the digital technology use variable index.